"EPOS" İN TURKISHCİNEMA - KÖKSAL, Selma (Atlas Journal, 2018)
EPOS, experimental protogonist(hero) drifting in the course of events In Turkish cinema we would look for the films, "Umut" "Hope" by Yılmaz Güney, "Anayurt Oteli""Hotel Motherland" by Ömer Kavur and "Uzak""far Away" by Nuri Bilge Ceylan